2019
DOI: 10.1128/iai.00765-18
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Gastric Mucin Triggers Toxin Production of Enteropathogenic Bacillus cereus

Abstract: Enteropathogenic Bacillus cereus causes foodborne infections due to the production of pore-forming enterotoxins in the intestine. Before that, spores have to be ingested, survive the stomach passage, and germinate. Thus, before reaching epithelial cells, B. cereus comes in contact with the intestinal mucus layer. In the present study, different aspects of this interaction were analyzed. Total RNA sequencing revealed major transcriptional changes of B. cereus strain F837/76 upon incubation with porcine gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 68 publications
1
24
0
1
Order By: Relevance
“…It was also found that swimming of different B. cereus strains was enhanced in the presence of mucin, and that these strains were able to actively move towards mucin, with swimming radius partially depending on the mucin concentration. This corresponded with a differential expression of genes involved in motility and chemotaxis upon contact with mucin, including flagellar and chemotaxis proteins [288]. Swimming and swarming motility, as well as bacterial pathogenicity, depends strongly on flagella [301,302,[306][307][308].…”
Section: Motility and Flagellamentioning
confidence: 84%
See 1 more Smart Citation
“…It was also found that swimming of different B. cereus strains was enhanced in the presence of mucin, and that these strains were able to actively move towards mucin, with swimming radius partially depending on the mucin concentration. This corresponded with a differential expression of genes involved in motility and chemotaxis upon contact with mucin, including flagellar and chemotaxis proteins [288]. Swimming and swarming motility, as well as bacterial pathogenicity, depends strongly on flagella [301,302,[306][307][308].…”
Section: Motility and Flagellamentioning
confidence: 84%
“…Mucin was also able to strain-specifically trigger germination of B. cereus spores, alone or in combination with heat treatment. Moreover, multiple genes involved in sporulation and germination were differentially expressed in B. cereus F837/76 upon contact with mucin [288]. In 2019, germination of 20 enteropathogenic and apathogenic B. cereus strains was comparatively analysed in CGY full medium, in RPMI 1640 cell culture medium and in cRPMI medium, which was pre-incubated with CaCo-2 cells and filtered.…”
Section: Germination Of Sporesmentioning
confidence: 99%
“…So far, all B. thuringiensis isolates in this study showed the genetic premises (presence of enterotoxin genes) to provoke the diarrhoeal type of food poisoning. Nevertheless, prerequisites for B. cereus enterotoxin production and cytotoxicity are also spore germination [ 14 , 40 , 41 , 42 , 43 ] and motility [ 14 , 44 , 45 , 46 ] in the host’s intestine.…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the potential health risk originating from (biopesticidal) B. thuringiensis isolates in more detail, we additionally investigated germination and motility behaviour of the strain set, which are further crucial prerequisites for the onset of the diarrhoeal disease [ 14 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Although different germination patterns emerged, spores of most isolates were able to germinate, even in cRPMI medium with preceding heat treatment mimicking re-heating of stored foods and subsequent consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This finding emphasizes the notion that mucin exerts its ability to enhance bacterial virulence through diverse mechanisms. In this regard, it has recently been shown that mucin enhances the virulence of enteropathogenic Bacillus cereus by upregulating the production of enterotoxin and other putative virulence factors (23). were i.p.…”
Section: Host Inflammatory Cell Responses To Ip Inoculation With Amentioning
confidence: 99%